Association Between Statin Use and Cardiovascular Events After Carotid Artery Revascularization. Issue 16 (21st August 2018) - Hussain, Mohamad A.; Saposnik, Gustavo; Raju, Sneha; Salata, Konrad; Mamdani, Muhammad; Tu, Jack V.; Bhatt, Deepak L.; Verma, Subodh; Al‐Omran, Mohammed
Abstract : Background: Statins are commonly used for the prevention of cardiovascular events; however, statins are underutilized in patients with noncoronary atherosclerosis. We sought to establish the rates of statin use in patients with carotid artery disease and to examine the association between statin therapy and outcomes after carotid revascularization. Methods and Results: In this population‐level retrospective cohort study, we identified all individuals aged ≥66 years who underwent carotid endarterectomy or stenting in Ontario, Canada (2002–2014). The primary outcome was a composite of 1‐year stroke, myocardial infarction, or death (major adverse cardiac and cerebrovascular events). Five‐year risks were also examined. Adjusted hazard ratios were computed using inverse probability of treatment weighting based on propensity scores. A total of 7893 of 10 723 patients (73.6%) who underwent carotid revascularization were on preprocedural statin therapy; moderate‐ or high‐dose therapy was utilized by 7384 patients (68.9%). The composite rate of 1‐year major adverse cardiac and cerebrovascular events was lower among statin users (adjusted hazard ratio: 0.76; 95% confidence interval, 0.70–0.83). Patients who were on persistent long‐term statin therapy after the carotid procedure continued to experience significantly lower risk of major adverse cardiac and cerebrovascular events at 5 years (adjusted hazard ratio: 0.75, 95% confidence interval, 0.71–0.80). The beneficial associations with statin use were observed regardless of type of carotid revascularization procedure, carotid artery symptom status, or statin dose. Conclusions: Continuous statin therapy was associated with a 25% lower risk of long‐term adverse cardiovascular events in patients with significant carotid disease. Along with other supportive evidence, statins should be considered in patients undergoing carotid revascularization, and efforts are required to increase statin use in this undertreated population.